REARING OF 'AYU' LARVAE (PLECOGLOSSUS ALTIVELIS) BY ARTIFICIAL DIETS. I. EFFECTS OF SOME VITAMINS AND ENZYMES SUPPLEMENTS ON GROWTH AND SURVIVAL - Sultana, N; Hossain, M A; Furuichi, M; Yone, Y (Indian Journal of Fisheries, 2011)
Ayu', Plecoglossus altivelis is the mostprized freshwater fish in Japan after eel.However, culture of this species is not widespread compared to other freshwater ormarine fishes. This is probably due to thecomplex life cycle of this species